Analisis Faktor-Faktor Yang Mempengaruhi Audit Report Lag Pada Perusahaan Manufaktur Di Indonesia (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - LISTIYANA, HENNY, Drs. Agus Endro Suwarno, M.Si (2017)
Audit report lag is the time period between the date of closing date of closing date until the reporting date of the independent auditors. This study aims to examine the influence of profitability, the audit opinion, solvency, company size, and reputation KAP to audit report lag in the period 2012-2014. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange period 2012-2014. Sample period of this study was determined by using purposive sampling method. The sample in this study amounted to 81 companies with outlier data is 11, so that the data obtained a sample of 70 companies. Analysis of data using the multiple linear analysis. Result showed that (1) the profitability not sigificant effect with the audit report lag (2) audit opinion significant negative effect with the audit report lag (3) solvability significant effect with the audit report lag (4) the size of company not significant influene with the audit report lag 95) the reputation of KAP not significant effect with the audit report lag.